2009
DOI: 10.1007/978-3-642-04133-4_14
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Usability in the Software Process: A Study of Irish Software SMEs

Abstract: Abstract. This paper explores the software processes and usability techniques used by Small and Medium Enterprises (SMEs) that develop web applications. The significance of this research is that it looks at development processes used by SMEs in order to assess to what degree usability is integrated into the process. This study seeks to gain an understanding into the level of awareness of usability within SMEs today and their commitment to usability in practice. The motivation for this research is to explore th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A lack of SPI focus is also observable in studies on UX integration. The closest studies to this topic are those that directly or indirectly report on the relation between integrating usability practices into software development processes and SPI [3], [7]. In a recent mapping study on product quality within SPI activities, Garcia-Mireles et al [8] have identified two studies with usability in focus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lack of SPI focus is also observable in studies on UX integration. The closest studies to this topic are those that directly or indirectly report on the relation between integrating usability practices into software development processes and SPI [3], [7]. In a recent mapping study on product quality within SPI activities, Garcia-Mireles et al [8] have identified two studies with usability in focus.…”
Section: Introductionmentioning
confidence: 99%
“…The study is performed in an action research setting where the researchers take an active role in improving the process to better support usability testing. Secondly, a study by Oconnor et al [7] that, through interviews with practitioners, investigates suitability of development processes for supporting usability.…”
Section: Introductionmentioning
confidence: 99%
“…SME [56], [57], [63], [66], [76], [85], [86], [93]- [95], [104], [105], [108], [110], [118], [123], [124] (c) Framework/standards 1 None [19], [23], [32], [35], [36], [63], [66], [68], [70], [78], [81], [83]- [87], [93], [94], [96]- [102], [104], [109], [118]…”
mentioning
confidence: 99%